T4N0M0 nasopharyngeal carcinoma patients: do they have a distinct tumor biology? - (:unkn) unknown (My University, 2010)
OBJECTIVES: To investigate the clinical manifestations and treatment outcomes of non-metastatic T4N0 nasopharyngeal cancer patients, and to compare them with other stage IVA subgroups of patients. PATIENTS AND METHODS: A retrospective analysis of 775 non-metastatic nasopharyngeal cancer patients, treated in four radiotherapy centers between 1990 and 2005, was undertaken. Among 197 stage IVA patients, 90 (11.6%) patients were staged as T4N0, 32 (4.1%) as T4N1, and 75 (9.7%) as T4N2. T4N0 patients constituted 40.8% of all T4 cases (median age 53 years; range 15 to 76 years). Cranial nerve involvement was detected in 59 (65.5%) of these cases. RESULTS: The median follow-up period was 38 months. There were only nine (10%) patients younger than 30 years of age with T4N0 tumors, for patients with diseases other than T4N0, 27.1% of the patients were under 30. Survival rates for five-year loco-regional progression free survival, distant failure free survival, and disease specific survival were 65.9%, 94%, and 71.4%, respectively. Distant failure free survival of T4N0 patients was more probable than for stage T4N1 (p=0.06) and T4N2 (p=0.008) patients. CONCLUSION: Non-metastatic T4N0 tumors have some distinct features, including a unimodal age distribution and a better distant failure free survival than the other subgroups of stage IVA. Therefore, it may be better to include T4N0 patients in stage III instead of stage IVA.
Keywords: Adult; Female; Humans; Middle Aged; Aged; Adolescent; Male; Retrospective Studies; Age Distribution; Disease-Free Survival; Survival Analysis; Neoplasm Staging; Neoplasm Metastasis; Cranial Nerves; Nasopharyngeal Neoplasms